Implementing trauma-informed pedagogies for school change : shifting schools from reactive to proactive - Stokes, Helen; Brunzell, Tom (Emerald studies in trauma-informed education, 2024)
The area of trauma-informed positive education (TIPE) is a recently emerging field in educational studies. Schools serving communities contending with educational inequity have many students identified as trauma-affected, with significant unmet learning and social emotional needs. This groundbreaking study and first book in the Emerald Studies in Trauma-Informed Education series is the first longitudinal research in trauma informed positive education, and the first research to link the professional learning and ongoing implementation of TIPE pedagogical practices to changed student perceptions of school and collective teacher efficacy over a four-year period. Providing examples of how schools implement TIPE and using case studies from two schools that were experiencing difficulty with their delivery of learning and wellbeing outcomes for students, the authors explore how implementing TIPE pedagogical practices can bring about school change. There is a focus on student wellbeing, collective teacher efficacy and assisting students to be ready to learn. The case studies that are explored will be of interest to school practitioners and system leaders working with students who are are not yet ready to learn and disengaged from school.